ADAPTATION OF ICT LEARNING IN THE 2013 CURRICULUM IN IMPROVING UNDERSTANDING STUDENT’S OF DIGITAL LITERACY - Dessy Putri Wahyuningtyas; Nanny Mayasari; Siti Rohmah; Erwinsyah Satria; Rinovian Rais (Jurnal Scientia, 2022)
The growth of information and communication technology (ICT) has a substantial positive impact on education. There is a technology disruption that creates changes and new discoveries due to technological affluence, so bringing about changes in education, particularly in the adaptation of the school's learning curriculum. ICT learning in curriculum 2013 has a favorable effect on ICT learning. In addition to boosting students' ability to comprehend and implement digital literacy, it is possible to express that the predicted benefits would also increase students' character education in preparation for the digital era. This study intends to assess the adaption of ICT learning in the 2013 curriculum, taking into account both the good and negative effects of technology on education, as well as the resources available to schools for implementing ICT learning. Become a proposal for the integration of ICT into the education system and schools, comprised of emerging, applying, integrating, and changing stages. So that it can serve as a model for applying ICT to improve student competence in utilizing information technology devices, as students require comprehension and digital literacy abilities in order to acquire improved competencies. According to the 2013 curriculum, it is anticipated that student competencies, particularly those linked to digital literacy competencies, will enhance as a result of this research.